Feasibility Study of Hybrid Power Plant in Panjang Island, Serang Regency, Banten - Dwaldes Bernad; Poetro Lebdo Sambegoro (ITB Graduate School Conference, 2025)
Panjang Island, located in Banten Province, Indonesia, is an isolated island currently powered by six diesel generator units. This research explores the techno-economic feasibility of integrating renewable energy sources, specifically photovoltaic (PV) systems and battery energy storage systems (BESS), into the island’s existing diesel infrastructure. A dual-simulation approach was adopted: PVsyst was utilized to evaluate the technical performance of the PV system based on site-specific solar resource data, while HOMER Pro was used to optimize the hybrid system configuration and assess its economic viability. The simulation results reveal that the hybrid Diesel-PV–BESS system can reduce the Levelized Cost of Electricity (LCOE) from IDR 3,698/kWh to IDR 2,815/kWh, yielding a 23.9% cost savings. Furthermore, the system achieves a renewable energy contribution of 94.1%, with a return on investment (ROI) of 9.1%, internal rate of return (IRR) of 13%, and a payback period of 6.9 years. These results indicate that the proposed hybrid system is techno-economically feasible, offering a promising solution for sustainable electrification. The results of this study serve as a valuable reference for PT PLN (Persero) and other stakeholders in advancing reliable and cost-effective energy access for isolated areas.